Differentiating Asian working holiday makers from traditional backpackers on the basis of accommodation preferences. (June 2018) - Nagai, Hayato; Benckendorff, Pierre; Tkaczynski, Aaron
Abstract: The Australian working holiday maker (WHM) program has contributed to the international youth travel market in Australia for many years. Despite a recent increase in the number of participants from Asian countries, their travel behaviours, including accommodation preferences, have not yet been fully explored. In fact, Asian WHMs have often been treated as backpackers in previous studies. The purpose of this study was to explore whether Asian WHMs differ from traditional backpackers on the basis of accommodation preferences. The study employed a sequential mixed methods design consisting of six focus groups followed by a self-administered questionnaire survey. Analyses of both the qualitative and quantitative data revealed that similar to European WHMs, backpacker accommodation was used by many Asian WHMs. However, a sizeable proportion of this market did not stay at this type of accommodation for reasons such as concerns about cleanliness and safety, cultural and language barriers and unfamiliarity with the style of accommodation. Whereas, shared accommodation with people from similar cultural backgrounds was a preferred accommodation style. The main implication of this study is that Asian WHMs cannot be fully understood when they are simply categorised as part of the wider backpacker market. Further consideration of their unique characteristics is required to obtain a comprehensive understanding of this cohort in the current youth travel market.